Exposure, perceived risk, and psychological distress among general population during the COVID-19 lockdown in Wuhan, China - Liu, Yujun; Liu, Linping; Shi, Zhilei (Frontiers in Psychiatry, 2023)
Introduction The COVID-19 pandemic that has been going on since the end of 2019 impacts people on both the physical and psychological levels. However, the psychological status, especially its underlying psychosocial mechanisms among the general population in Wuhan, the earliest epicenter and hardest-hit city in China during the pandemic, has not been well investigated. This study aimed to examine the relationships between exposures, perceived risk, and psychological distress among the general population in Wuhan during the COVID-19 lockdown. Methods Data were from a cross-sectional online survey conducted from 20 February to 4 March 2020. Final analyses included 4,234 Wuhan respondents. A 5-item Hopkins Symptom Checklist was adopted to assess respondents’ psychological distress. Results It was found that nervousness, fear, and worry were the most common symptoms among Wuhan residents during the lockdown. Exposure within a close physical distance, exposure within the social network, and perceived risk are significantly positively related to respondents’ psychological distress. Moreover, perceived risk mediated the effects of exposures on respondents’ psychological condition. Discussion These findings conduce to identify the populations at higher risk of suffering psychological disturbance during the pandemic and are expected to inform the policymakers and mental health professionals to monitor and improve the perception of risk among the target population by appropriate interventions.